Developing Pearl Millet Seed Parents Adapted to Arid Regions of North-Western India - Manga, V K; Kumar, Arun (Annals of Arid Zone, 2016)
Rajasthan contributes about 50% to area and 42% to the production of pearl millet in the country. Despite release of large number of hybrids in the country, area under high yielding cultivars in the arid western Rajasthan is about 25%. For hybrids to be successful in the arid region, it is important that the hybrids are developed using parents that are downy mildew resistant and adapted to the harsh climatic conditions of this region. CAZRI has a strong restorer (male parents) development program, but lacked in development of male sterile lines. Hence a targeted program was initiated in 2002 for the development of B lines (maintainer lines) adapted to arid conditions. Twenty B lines of identified promising A lines were crossed in a diallel fashion. A composite was constituted from these crosses and progenies were selected and advanced by selection. Similarly from eighteen promising crosses, segregating populations were developed. Promising plants were self selected from these populations to develop B lines. These B lines were crossed with male sterile lines ICMA 95111 and ICMA 94555 having A1 cytoplasm and ICMA 97555 having A4 cytoplasm. The F1s were backcrossed with the recurrent parents up to BC6 to develop sixteen male sterile lines in the year 2010. Evaluation of new ms lines revealed presence of sufficient variability for various agronomic traits. Crossing new ms lines with inbred restorers has given promising hybrids that have been contributed to the coordinated trials. Key words: Pearl millet, Pennisetum glaucum, ms lines, arid region.